2016
DOI: 10.1515/bhk-2016-0015
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for the sprint performance in male football players aged from 9–35 years

Abstract: SummaryStudy aim: The aim of the present study was twofold: firstly, to examine the effect of age on a 20 m sprint performance; and secondly, to establish normative data for the 20 m sprint performance by age in football players. Conclusions: In summary, the speed ability of the football players improved with age until 15 years old, where it reached its peak. On the other hand, the other age groups U16 to U35 revealed no major differences in the speed over a 20 m sprint. The reference values presented in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 58 publications
4
27
0
1
Order By: Relevance
“…According to Nikolaidis et al [25], sprint ability is a major component of performance and can be used in talent identification and in the selection of players. However, the results of the present study differ from the findings of Dal Pupo et al [8], who found a correlation between the vertical jump test, sprint test, and agility test in young soccer players.…”
Section: Discussionmentioning
confidence: 99%
“…According to Nikolaidis et al [25], sprint ability is a major component of performance and can be used in talent identification and in the selection of players. However, the results of the present study differ from the findings of Dal Pupo et al [8], who found a correlation between the vertical jump test, sprint test, and agility test in young soccer players.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that, in addition to the anthropometric characteristics and the physical qualities analyzed in the present study, other variables are also adjuvant to athletes' competitive success, such as technical and tactical performance [13], sprint velocity [22,29] and the number of interchanges during a match [3,24].…”
Section: Discussionmentioning
confidence: 92%
“…Football is one of the most popular team sports in the world, and millions of athletes practice it regularly as members of football clubs [1]. Among the physical parameters, the sprint ability, especially combined with short periods of recovery [2,3], is one of the most important elements, as it can discriminate football players into different levels [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The football match analysis indicated that sprints over short distances are generally performed 17-81 times per match, and represent 8-12% of the distance covered by the players [1]. It is stated that during a soccer game, many of the sprints done with maximum power are generally straight and the sprint distance changes between 5-50 meters [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation